Incidence and predictors of mortality among children with severe acute malnutrition admitted to therapeutic feeding units in Ethiopia: a systematic review and meta-analysis - Amanuel Adugna; Gossa Fetene Abebe; Desalegn Girma; Melsew Setegn Alie (BMJ Open)
Objective To estimate the mortality rate and identify predictors of mortality among under-five children with severe acute malnutrition (SAM) admitted to therapeutic feeding units (TFUs) in Ethiopia.Methods We searched PubMed, HINARI, Science Direct, Google Scholar and African Journals Online from 1 March to 30 May 2024. The Joanna Briggs Institute checklist was used to appraise the included studies. Heterogeneity was identified using I2 statistics. Funnel plots and Egger’s tests were used to determine publication bias.Results Out of 1085 studies, 15 were included in this analysis. The pooled mortality rate among under-five children with SAM admitted to TFUs in Ethiopia was 8.32 per 1000 person-days of observation (95% CI: 6.25 to 11.06). The mortality rate has not changed over time. HIV infection (HR: 2.84; 95% CI: 1.25 to 6.42), tuberculosis (HR: 1.86; 95% CI: 1.35 to 2.56), intravenous fluid use (HR: 3.37; 95% CI: 2.39 to 4.75), altered body temperature (HR: 4.47; 95% CI: 1.90 to 10.51), impaired consciousness (HR: 2.91; 95% CI: 1.94 to 4.37), not receiving F-100 supplementation (HR: 4.51; 95% CI: 3.25 to 6.26), shock (HR: 4.20; 95% CI: 2.92 to 6.04), and nasogastric tube feeding (HR: 2.02; 95% CI: 1.67 to 2.44) were predictors of mortality.Conclusion The pooled mortality rate in Ethiopia was 8.32 per 1000 person-days, and it has not decreased over time. Most of the identified factors are related to comorbidities and complications of SAM, as well as nutritional therapy. Thus, it is essential to strengthen nutrition policies, programme implementation and healthcare services, which focus on the timely management of SAM complications, integrated care for comorbidities and improved F-100 supplementation.PROSPERO registration number CRD42024555014.